1999
DOI: 10.1099/0022-1317-80-5-1141
|View full text |Cite
|
Sign up to set email alerts
|

Complete sequence and genome properties of Chinese wheat mosaic virus, a new furovirus from China.

Abstract: The complete nucleotide sequence of a virus infecting winter wheat in Shandong province, China has been determined. This was previously thought to be soil-borne wheat mosaic virus but, while the two viruses are related, they are only 75 % (RNA1) and 63 % (RNA2) identical at the nucleotide level, while the amino acid sequences share from 62 % (19 kDa RNA2 product) to 84 % (RNA1 replicase) identity. The analysis shows that the Chinese virus should be considered a new member of the genus Furovirus and has been na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
57
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 9 publications
0
57
0
1
Order By: Relevance
“…The putative methyltransferase region was most similar to sequences of Soil-borne cereal mosaic virus (Diao et al, 1999a;Koenig et al, 1999), Soil-borne wheat mosaic virus (Shirako & Wilson, 1993;Ratti et al, 2004) and Oat golden stripe virus (Diao et al, 1999a) (unassigned members of Furovirus), Fragaria chiloensis latent virus (Tzanetakis & Martin, 2005) (Bromoviridae: Ilarvirus), Chinese wheat mosaic virus (Yang et al, 2001;Diao et al, 1999b) (unclassified Furovirus) and Pepper mild mottle virus (Velasco et al, 2002; GenBank accession no. BAD90599) (unassigned Tobamovirus), and the expect value ranged from 3.5E-06 to 6E-03.…”
mentioning
confidence: 79%
“…The putative methyltransferase region was most similar to sequences of Soil-borne cereal mosaic virus (Diao et al, 1999a;Koenig et al, 1999), Soil-borne wheat mosaic virus (Shirako & Wilson, 1993;Ratti et al, 2004) and Oat golden stripe virus (Diao et al, 1999a) (unassigned members of Furovirus), Fragaria chiloensis latent virus (Tzanetakis & Martin, 2005) (Bromoviridae: Ilarvirus), Chinese wheat mosaic virus (Yang et al, 2001;Diao et al, 1999b) (unclassified Furovirus) and Pepper mild mottle virus (Velasco et al, 2002; GenBank accession no. BAD90599) (unassigned Tobamovirus), and the expect value ranged from 3.5E-06 to 6E-03.…”
mentioning
confidence: 79%
“…These viruses are transmitted to the roots of their host plants by Polymyxa graminis Led., a soil-borne plasmodiophorid protist that can preserve its infectivity in soil for 10 years or more (Rao and Brakke 1969;Kendall and Lommel 1988). SBCMV is prevalent in Europe, CWMV in Asia, and SBWMV (the furovirus type member) in North America (Diao et al 1999;Kanyuka et al 2003;Ratti et al 2005;Budge et al 2008). In Italy, SBCMV is widespread in the main wheat growing areas, and especially in the northern and central regions of Italy, where it causes grain yield losses often above 50% on susceptible cultivars of durum wheat (AABB genome) and common wheat This thus suggests that this cultivar and its derivatives carry a major gene or gene-block for SBCMV resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Bars below the aa sequence alignment indicate identified NLSs. +, Amino acid positions of 16K PpK20 PS mutants displaying tolerance (class I and II mutants) to pentapeptide insertions in silencing suppression ability; $, 16K residues highly conserved between CRPs derived from different virus genera (Morozov et al, 1989;Savenkov et al, 1998;Diao et al, 1999;Te et al, 2005). TRV 16K-PpK20 (GenBank accession no.…”
Section: Subcellular Localization Of Trv 16kmentioning
confidence: 99%
“…Thus, it can be concluded that the 16K suppression of gene silencing is organism-specific, depending on the assay applied. It is well-known from several previous studies that CRPs from different plant RNA viruses possess only distant sequence homology relationships (Koonin et al, 1991;Savenkov et al, 1998;Diao et al, 1999;Te et al, 2005). This homology is mainly restricted to a conserved motif (Cys-Gly...Cys-Gly-X-X-His, see the tobravirus CRP alignment in Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation